Alagille syndrome due to a de novo NOTCH2 mutation presenting as prenatal oligohydramnios and congenital bilateral renal hypodysplasia: A case report - Xu, Fengdan; Peng, Qi; He, Xiaoguang; Chen, Xiaolan; Jiang, Shuanglan; Lu, Xiaomei; Li, Ning (Frontiers in Pediatrics, 2022)
Introduction: Here, we report the case of an infant suffering with Alagille syndrome (ALGS) manifesting with the atypical clinical manifestations of prenatal oligohydramnios and renal lesions. To the best of our knowledge, this is the first case of ALGS presenting as prenatal oligohydramnios and renal lesions caused by a de novo variant of the NOTCH2 gene. Case presentation: A 3-month-old male infant was hospitalized for severe malnutrition. He presented with prenatal oligohydramnios from 28+4 weeks-of-gestation. After birth, he failed to thrive and suffered from impaired motor development, thermoregulation disorders, congenital bilateral renal hypodysplastic, initial stage 5, then improving to stage 3 chronic renal impairment, slightly elevated levels of transaminases, cholestasis and dysmorphic facial features. We used a diagnostic screening panel of 4047 pathogenic genes and whole exome sequencing (WES) to analyze the proband and his parents (who had normal kidneys). We found that the proband carried a de novo heterozygous splicing variant (c.5930-2A > G) in intron 33 of the NOTCH2 gene. Transcriptome sequencing confirmed that the mutation of this gene site would affect the splicing of NOTCH2 mRNA and lead to exon 33 skipping. Conclusions: Our case expands the spectrum of pathogenic variants of the NOTCH2 gene that are known to be associated with ALGS and characterized by prenatal oligohydramnios and renal lesions. It also reminds us of the necessity to monitor the liver and kidney function of the infant if his/her mother has oligohydramnios during pregnancy, and recommend ALGS as additional differential diagnosis in prenatal renal abnormalities.